Exploration and Comparison of No-Code AI for Website Development - Cheerapakorn, Salintip (Journal of Applied Statistics and Information Technology, 2025)
In an era where Artificial Intelligence (AI) is rapidly advancing, the use of AI-powered website builders has become a popular choice in 2024. These tools enable users to create websites quickly without requiring technical expertise or prior knowledge of coding. As a result, AI-driven website builders have emerged as a convenient and efficient solution for both business owners and general users seeking high-quality websites. A review of AI-based website creation tools in 2024 reveals that WIX, Jimdo, and Hostinger are the most popular platforms, each offering distinct features while all providing the common advantage of enabling fast and effective website creation. WIX is noted for its flexibility in design and a wide range of functions, Jimdo is tailored for small businesses with its focus on ease of use and speed, and Hostinger offers affordable web hosting services combined with user-friendly website building tools. Choosing the most appropriate tool for website creation should be based on features that align with the specific needs of the website, budget, and user convenience. Additionally, reading reviews and feedback from actual users is an important factor in making an informed decision on the best platform for website development.